Patient-Specific Modeling in Tomorrow's Medicine - Gefen, Amit.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book reviews the frontier of research and clinical applications of Patient Specific Modeling, and provides a state-of-the-art update as well as perspectives on future directions in this exciting field. The book is useful for medical physicists, biomedical engineers and other engineers who are interested in the science and technology aspects of Patient Specific Modeling, as well as for radiologists and other medical specialists who wish to be updated about the state of implementation.
Fundamental concepts -- Experimental methods -- Computational modeling -- Mechanobiology in cancer.
Keywords: Engineering; Radiology, Medical; Biomedical engineering; Biomaterials; Engineering; Biomedical Engineering; Medical and Radiation Physics; Diagnostic Radiology; Biomaterials